2015
DOI: 10.3109/10715762.2014.999674
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin ameliorates streptozotocin-induced liver damage through modulation of endoplasmic reticulum stress-mediated apoptosis in diabetic rats

Abstract: We investigated the effect of curcumin on liver injury in diabetic rats induced by streptozotocin (STZ) through modulation of endoplasmic reticulum stress (ERS) and unfolded protein response (UPR). Experimental diabetes was induced by a single intraperitoneal injection of STZ (55 mg/kg), and curcumin was given at 100 mg/kg by gavage for 56 days. We observed that curcumin improved the morphological and histopathological changes, significantly decreased hepatic ERS marker protein: glucose-regulated protein 78, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 71 publications
3
34
0
Order By: Relevance
“…In addition, curcumin displays a specific ability to ameliorate ER stress (Afrin et al, 2015; Rashid and Sil, 2015; Wang et al, 2016). In the present study, we found that curcumin supplementation significantly mitigated palmitate-induced insulin resistance ( Figures 1C–E ) and suppressed palmitate-stimulated ER stress/JNK/IRS-1 signaling in HUVECs ( Figure 4 ), suggesting that curcumin reverted palmitate-induced insulin resistance of HUVECs by inhibiting ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, curcumin displays a specific ability to ameliorate ER stress (Afrin et al, 2015; Rashid and Sil, 2015; Wang et al, 2016). In the present study, we found that curcumin supplementation significantly mitigated palmitate-induced insulin resistance ( Figures 1C–E ) and suppressed palmitate-stimulated ER stress/JNK/IRS-1 signaling in HUVECs ( Figure 4 ), suggesting that curcumin reverted palmitate-induced insulin resistance of HUVECs by inhibiting ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…As a traditional Chinese formula consisting of multiple compounds, Xiaoyaosan targets both depression and diabetes. The constituent chemical compounds, such as paeoniflorin, liquiritin, curcumin, and saikosaponins A and C, are active ingredients as antidepressants [ 22 26 ], while curcumin and paeoniflorins have antidiabetic effects [ 27 – 30 ]. The HPLC-LTQ-Orbitrap-MS chromatogram results showed that the eight compounds, including paeoniflorin, liquiritin, glycyrrhizic acid, ferulic acid, saikosaponins A and C, curcumin, and Poria cocos alcohol derived from Radix Paeoniae Alba, liquorice, Angelica sinensis , Radix Bupleuri, fresh ginger, and Poria cocos , respectively, could match corresponding peaks of reference standards by the same HPLC-LTQ-Orbitrap-MS eluted system.…”
Section: Discussionmentioning
confidence: 99%
“…The intake of overdose drugs may cause severe side-effects, like hepatoxicity. Curcumin has been reported to ameliorate streptozotocin-induced liver injury of diabetic rats by decreasing hepatic endoplasmic reticulum stress marker protein and the sub-arm of unfolded protein response signaling protein, and inhibiting TNF-α, IL1β, phospho-p38 MAPK, and ASK1 in liver [ 116 ]. Paracetamol-induced mitochondrial dysfunction in hepatocytes is also attenuated by curcumin.…”
Section: Health Benefits Of Curcuminmentioning
confidence: 99%